Nasolabial interpolation flap for nasal alar reconstruction after skin tumor resection - Rafael Luís Sakai; Luis Carlos Vieira Tavares; Carlos Alberto Komatsu; Leão Faiwichow (Revista Brasileira de Cirurgia Plástica)
Introduction: The nose is a common site for skin neoplasms. Due to its functional and esthetic importance, nasal reconstruction, mainly that of the nose ala, is challenging. The objective is to describe the nasolabial interpolation flap for nasal alar reconstruction after skin tumor resection. Methods: Patients with nonmelanoma skin tumors on the nasal ala without involvement of the alar and supra-alar sulcus underwent reconstruction with a nasolabial interpolation flap associated with conchal cartilage grafting. Details of the surgical planning and operative sequence and an analysis of the results are presented. Resultados: In the treatment of skin tumors on the nasal ala, results from the oncological and esthetic point of view should be sought, i.e., maintenance of the three-dimensional structure and cutaneous features should be intended. Conclusion: Use of the nasolabial interpolation flap was effective for nasal alar reconstruction despite the need for two surgeries.